PRODUKSI SERASAH MANGROVE DI KAWASAN PESISIR KABUPATEN ACEH JAYA - Dewi Fithria; Chairudin Chairudin (Universitas Teuku Umar, 2018)
Mangrove litters like leaves, branches and fruit will partly sunk under its own weight and blown by the currents of the ocean when sink back again to normal. Litter is carried away a current of who will be the organic matter and capable of being increases the production of litter yielded become an important factor in the transfer of hara of its vegetation those mangrove trees into the ground. This study aims to in order to understand the the production of mangrove litter in the area of those mangrove trees in Aceh Jaya. This research is right beside the road explorative and descriptive. The determination of the study locations is based on a method of purposive the sampling method of that has been assumed represent the regions of this research. The research results show the production of litter hutan mangrove in the remote and sparsely populated Rigaih of environmental friendly of the district of Aceh Jaya as much as 9.85 tons on higher demand for/ than one hectare in size/years. The type of whichdominant who gives hara of the largest memorials in hutan mangrove this is Rhizophora stylosa with the volume of production as much as litter 5.27 tons on higher demand for/than one hectare in size/years or about 53%. The parameter of the physical environment of to exert an influence upon the production of litter hutan mangrove in the area of environmentallyfriendly Aceh Jaya district. Keywords : environmentally friendly area, mangrove ecosystem, production litter